358. How much treatment suspension or scheduling delay in treating gynecological cancer affects survival?. (December 2018) - Siciliano, R.; Piro, F.; Cosentino, D.; Massenzo, A.; Marafioti, L.
Abstract : Purpose: To evaluate impact of break in treatment for nonmedical reasons, as delay in scheduling BRT boost, on survival in gynaecological cancer. We estimated Overall Treatment Days (OTD) of each patient. Methods: By November 2008 to April 2012 95 endometrial cancer pts. treated in adjuvant according to this schedule: ERT (50 Gy/5 weeks) plus BRT boost 18 Gy in 3 fractions before or after same ERT. For patients of our Center performed boost before, patients from nearby centers boost performed after. Generally OTD was longer in patients who performed boost after ERT (pts. of nearby centers were sent for boost after ERT). The gap after ERT result median delay 35 days (range 7–134). We evaluated this factor in comparison of survival curves with Kaplan Meier method. Results: Median follow-up 6, 35 years (range 1, 13–8, 33). In evaluation of survival according value of OTD cut-off result is ⩾70 days. We recorded two groups Median-55 (40–68) of 70 pts. vs Median-96 (72–159) of 25 pts. Survival comparison that considered Median-55 vs Median-96 resulted favourable first group and more significant, median 5, 67 vs. 4, 79 years (P = 0, 21). Conclusions: Reduce to minimum entire treatment time is mandatory. For better quality management of entire treatment (avoiding treatment suspension for nonmedical reasons) we need to increase collaboration with nearby centers to be more effective (scheduling BRT simulation before the ERT at own center). Patients who have ended the ERT often come for BRT simulation to our center with problems of acute toxicity in progress so to perform boost is very difficult. Because of pain that can be caused during CT simulation it is possible to have a missing target, to avoid this problem pts. of our center have simulation CT at same time of ERT simulation. By increasing quality management survival increases.